Slurry erosion behaviour of thermomechanically treated 16Cr5Ni stainless steel. (March 2018) - Kishor, Brij; Chaudhari, G.P.; Nath, S.K.
Abstract: 16Cr5Ni martensitic stainless steels are used for making underwater parts of hydro turbines, which suffer severe attack from sand particles during service. The effect of thermomechanical processing that can potentially improve the mechanical properties of steels on the slurry erosion behaviour is studied. Hot compression tests were performed at strain rates of 0.001 s −1 and 10 s −1 at 950 °C and 1050 °C for a true strain of 0.7. The erosion test is conducted in a slurry pot erosion tester for 24 h at room temperature. Thermomechanically processed specimens exhibited enhanced slurry erosion that is attributed to its lower toughness arising from typical microstructural features. The erosion mechanism is correlated with the microstructure, hardness and tensile properties. Highlights: 16Cr5Ni stainless steel is thermomechanically treated. After treatment, retained austenite is reduced. δ-ferrite and retained austenite altered the mechanical properties. Slurry erosion involved material removal by fatigue. Processed specimens showed lower slurry erosion resistance.